EFEITOS DO RESVERATROL NA CAQUEXIA INDUZIDA POR TUMOR. - VICTOR, Elis Cabral (2021)
Cancer appears in Brazil as the second leading cause of death in recent years. Neoplastic cachexia is a syndrome that contributes to higher rates of morbidity and mortality, in addition to reduced quality of life. Previous studies describe that mice with solid Ehrlich tumor showed muscle loss, evolving to a cachectic condition after 14 days of inoculation, and this in vivo study model is applicable in the study of drugs with antitumor potential. Resveratrol (RSV) is a polyphenol found in foods, such as grapes and peanuts, and has been studied in the treatment of several neoplasms. However, despite promising data on antitumor activity, there are no studies with this compound in neoplastic cachexia. The objective was to evaluate the effects of RSV on cachexia in a solid Ehrlich tumor model under treatment associated or not with chemotherapy. For an assessment of cachexia in the in vivo model, male Swiss mice aged 50 to 60 days were divided into two groups (n = 10): Normal (without treatment and without tumor) and the negative control group (inoculated with 2x107 tumor cells / mL without foot pad, without treatment). The results impaired that even maintaining body weight, the increase in the tumor accompanied a lower consumption of feed, loss of muscle mass and adipose tissue compared to the control group, suggesting the condition of neoplastic cachexia. To assess the effect of the treatment, part of the animals were inoculated with a tumor, as previously described, and divided into: Negative control (without treatment); Positive control (treated with 25 mg / kg cyclophosphamide, intraperitoneal for 14 days); RSV Group (10mg / kg, per gavage for 14 days); and RSV and Cyclophosphamide Group (10mg / Kg and 25mg / kg, by gavage and intraperitoneal, respectively), and a group of animals without tumor and treated with Resveratrol in the same dosage. The results impaired that RSV reduces tumor growth in the same way as cyclophosphamide. However, chemotherapy reduces the cellularity of lymphoid organs and increases serum levels of TNF-α and IL-6 and reduces MCP1, leading to greater muscle loss, while RSV reduced TNF-α and increases muscle mass without causing cytokinesis. and hepatotoxicity. Treatment with RSV and cyclophosphamide improves muscle weight compared to cyclophosphamide, but does not alter the immunosuppressive effects. The presence of sFasL appears to be a mechanism associated with tumor-mediated inflammation. The RSV, without tumor inoculation, increases the number of muscle fibers and does not alter immunological and hepatic parameters, suggesting low toxicity. The results suggest that in addition to the anti-tumor effect, RSV has anti-inflammatory activity capable of preserving muscle in neoplastic cachexia, however without effect on the mechanisms of muscle loss induced by chemotherapy, therefore, the present study ratifies the anti-tumor effect of RSV and shows its potential in the treatment of neoplastic cachexia.